Evaluation of circulatory and salivary levels of heat shock protein 60 in periodontal health and disease - R Ramya Nethravathy; Swarna Alamelu; K V Arun; TSS Kumar (Wolters Kluwer Medknow Publications, 2014)
Background: Self-antigens such as heat shock protein 60 (HSP 60) have recently been implicated in the periodontal disease pathogenesis. There is scant evidence regarding HSP 60 levels in circulation and saliva following periodontal disease and its possible relation to systemic inflammation. Aim of the Study: The aim was to evaluate the circulatory and salivary levels of HSP 60 in periodontal health and disease and to correlate it with high sensitivity C-reactive protein (hs-CRP). Materials and Methods: Forty-five peripheral blood samples were collected from two groups of patients (periodontally healthy - Group A [22 patients] and periodontal disease - Group B [23 patients]). Serum, cell lysates, and saliva samples were used to detect HSP 60 levels in both groups by enzyme linked immunosorbent assay technique. Measurement of hs-CRP was performed using an immunoturbidimetric assay. Statistical analysis was done using the student t-test and Pearson's correlation. Results: Circulatory HSP 60 was significantly increased in periodontal disease compared to health (P - 0.038). There was a significant correlation between the totals circulating HSP 60 and hs-CRP (P - 0.052), but there was no significant correlation between the salivary HSP 60 and hs-CRP levels in periodontal disease. Conclusion: Circulating HSP 60 levels may play a role in the systemic inflammatory state produced by periodontal disease. Salivary HSP 60 may not be used as a surrogate to determine systemic inflammation.